Role of Directorates in Promoting Nursing and Midwifery Across the Various States of India: Call for Leadership for Reforms - Rajni Bagga; Vaishali Jaiswal; Ritika Tiwari (Wolters Kluwer Medknow Publications, 2015)
Background: While the roles and responsibilities of nursing professionals have multiplied over the years, but there are huge concerns with regard to the development of the nursing workforce and human resources (HR) issues for their career growth. The major lacuna is in not involving the nursing professionals in policy framing and decision-making. As a result, there is a leadership crisis of the nursing workforce across India. Objectives: The paper, is part of the WHO supported study, entitled "Study on Nursing and Midwifery in India: a critical review", is developed with the objective to review the current organizational and management structure for the nursing positions at the State Directorates in India and obtain a Leadership perspective to strengthen nursing management capacities to address maternal health issues. Materials and Methods: The study descriptive and qualitative in nature and the sources of information were both primary and secondary collected from 16 states of India. Results: Since none of the states have neither a Nursing Cell nor the post of Director Nursing, final decision-making powers rest with state health secretaries and medical directors. The nursing management structure majorly managed by senior policy makers from the medical fraternity, and provides very little scope for nursing professionals to participate in policy decision making to bring about reforms. There is no uniformity on HR issues concerning career graphs and pay structures across the states. Conclusions: In order to strengthen nursing as a profession and for facilitating their role at the policy level, more powers and autonomy needs to be given to them and this requires HR policy guidelines for nurses. Setting up a separate nursing directorate, to be headed by a senior nursing professional, is suggested in every state along with a strong nursing division at the National level. This total paradigm shift will empower nursing professionals to take up the leadership role at the policy level to bring about necessary reforms. Across the country, nursing professionals repeatedly echoed one requirement: To reframe nursing leadership at all levels.